A Study on Clinical Governance and Awareness in Quality Standards in Health from the Perspective of Nursing Management - Sarıakçalı, Nuriye; Biçer, Enis Baha (My University, 2023)
Nurses, who are seen as the focal point in the implementation of clinical governance, have great importance in terms of knowledge, awareness, issues that they consider as obstacles and difficulties, and their suggestions for solutions. With this study, the clinical governance knowledge and awareness levels of the working nurses were examined, and it was aimed to contribute to the literature on the best practice of clinical governance by taking their opinions and suggestions. The population of the research consists of 716 nurses working in Sivas Health Services Application and Research Hospital. Questionnaires were collected both online and face-to-face. The responses of 122 nurses who voluntarily participated in the study were included in the study. The study was carried out with a mixed method and both qualitative and quantitative research methods were used. The study included 4 demographic questions and 9 questions about education, work, and knowledge level. In the literature, McSherry et al. (2012), Wallace et al. (2001) 4 Likert-type items were conveyed about the obstacles to clinical governance in their studies, and 2 open-ended semi-structured interview forms were used to determine their opinions and suggestions. In the study, which was shown as an obstacle to clinical governance and was found to be significant as a result of the analysis, the mean score of information technologies, lack of finance, and time was 1.72±0.79, the mean score of negative attitude towards research related to evidence-based practice was 2.07±0.89 The mean score for education and organizational culture change requirement was 1.83±0.85, and the mean score for cultural resistance to change was 2.02±1.04. Considering these values, it was determined that all expressions had a high level of disability score average.
Keywords: Awareness; Nurses; Quality in Healthcare; Clinical Governance